Sistem Monitoring Kelembaban Tanah, Kelembaban Udara, Dan Suhu Pada Lahan Pertanian Menggunakan Protokol MQTT - Arista Budi Setyawan; Mochammad Hannats Hanafi Ichsan; Gembong Edhi Setyawan (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Agriculture is one of the most important sectors to increase the economic growth of the Indonesian people. One of the most important factors in agriculture is the quality of agricultural land. To find out the quality of agricultural land regularly, the monitoring system of agricultural land using the MQTT protocol can be designed as a system that can monitor agricultural land in real time. This system is made using a soil moisture sensor which serves to read the value of soil moisture and also the DHT-11 sensor which serves to read values ​​from air humidity and temperature. Soil moisture sensor reads moisture with values ​​between 0-1300. As high as the value, the condition of the soil will get drier, if the value is lower then the soil conditions get wetter. For the DHT-11 sensor the first can read the value of air humidity that has a range between 0-100. The higher the value of the sensor reading, the higher the humidity value. For the second, it is to read the ambient temperature with units of degrees Celsius. The range of values ​​on this sensor reading is 0-100. The higher the value of the sensor readings, the higher or more heat the environment temperature. The sensor is processed by the Arduino microprocessor. The ESP8266 wifi module as the data sender to the IoT platform will be displayed on the Thingsboard webserver. Data from sensor readings are displayed in the form of diagrams, graphs and also real time conditions. From the implementation of the system, it can be concluded that this system can work optimally because it can display the results of reading sensor values ​​that can be displayed on the Thingsboard webserver.